PERAN KOMPENSASI, LINGKUNGAN KERJA, DAN DUKUNGAN PIMPINAN DALAM MENINGKATKAN SEMANGAT KERJA - Paeno, Paeno; Finatariani, Endah; Mawardi, Syamsi (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
For employees, carrying out duties properly is an obligation. But in practice, maintaining work performance and productivity is not easy. Therefore, factors that strengthen morale are needed, including a good compensation system, a comfortable working environment, and getting support from the leadership. In fact, this study will analyze these three factors, in order to determine the level of employee motivation. For this reason, a quantitative approach is determined, in order to obtain a statistical picture of the level of employee morale. In testing, multiple regression techniques are used. The research subjects were employees of PT Panin Bank, with a sample size of 52. The research data were obtained by distributing questionnaires. The results suggest that compensation is the factor that is considered the most influential on morale. This finding confirms that an employee will work better if his main goals are met. In a work context, the main goal of employees is compensation. It can be concluded, compensation can be used as an organizational strategy in directing and controlling employees so that they work in accordance with the interests of the company. Keyword : Motivation, Compensation, Environment, Leadership